Karakteristik Fisik Tepung Talas Bentul (Xanthosoma Sagittifolium) Termodifikasi Berdasarkan Waktu Fermentasi Dan Jenis Ragi Yang Digunakan - Nendra Prasetya, Hendrikus; Arlinda Sakerebau , Fransiska (Fakultas Pertanian, 2023)
Taro (Xanthosoma sagittifolium) is a food crop from tubers that is widely cultivated in Indonesia. Starch is a food ingredient that has a function in the food processing industry which functions as a determinant of product characteristics. Starch consists of two components that can be divided into two, namely amylose and amylopectin. Real starch or natural starch (without modification process) has limitations in food processing because it has viscosity, is less clear, and produces unwanted gels. In general, modified starch is used because it has functional properties that are not possessed by natural starch, such as viscous power, emulsion power and absorption power. The fermentation process in the processing of foodstuffs is by using microorganisms in a controlled manner to produce food ingredients by producing acids and alcohol to produce food products with good quality and value. This study used a 2x3 Factorial Design in a Complete Randomized Design (RAL) consisting of 2 factors, namely factor I type yeast consisting of 2 levels ( baker's yeast and yeast tape) and factor II fermentation time consisting of 3 levels ( 12 hours, 24 hours and 48 hours), each treatment was repeated 3 times. The results of the white degree show there is a markedly different influence on the influence of the interaction between the influence of fermentation time and yeast type. On viscosity there is no noticeable different influence on the modified starch characteristics of taro. On amylose levels there is also no real different influence, but on the influence of fermentation time there is a real different influence. On solubility there is no real different influence on the characteristics of taro starch, whereas in swelling power there is also no real different influence but there is a real influence on the type of yeast